Self-efficacy towards inclusion among physical education teachers with and without an undergraduate adapted physical education teaching minor - Triezenberg, Thomas N. (My University, 2014)
Research is limited on physical education (PE) for students with disabilities (SWD) who are homeschooled. Less is known about parental opinions regarding PE for them. This study gathered data about homeschooling curriculum requirements (i.e., PE) for SWD and data from parents regarding perceptions of the importance of PE in a homeschooling curricuhun. An online survey identified statutes regarding PE for homeschooled SWD and opinions about PE. A survey to parents who homeschool determined opinions about PE, how the service is provided, and its perceived importance. Results of the national survey found that 11 of 28 respondent states required subject areas for homeschooled students. Of those states, the required subjects were the same for students with and without disabilities, and PE was a required subject area for SWD in 6 states. The parent survey revealed PE was an important subject, PE was mostly provided by the parent or community-based services, and PE was somewhat important relative to other subjects. Both groups surveyed felt fundamental motor skills were the most important content area for homeschooled SWD, while team sports were least important. Further research is needed to determine how professionals can disseminate information to parents to improve PE experiences for homeschooled SWD.
Keywords: Inclusive education; Physical education teachers--Training of; Physical education for children with disabilities--Evaluation